2022
DOI: 10.3389/fneur.2022.998904
|View full text |Cite
|
Sign up to set email alerts
|

Reversing painful and non-painful diabetic neuropathy with the capsaicin 8% patch: Clinical evidence for pain relief and restoration of function via nerve fiber regeneration

Abstract: IntroductionCurrent oral treatments for pain in diabetic peripheral neuropathy (DPN) do not affect the progression of DPN i.e., “disease modification.” We assessed whether Capsaicin 8% patch treatment can provide pain relief and also restore nerve density and function via nerve regeneration, in both painful (PDPN) and non-painful (NPDPN) diabetic peripheral neuropathy.Methods50 participants with PDPN were randomized to receive Capsaicin 8% patch Qutenza with Standard of Care (SOC) (PDPN Q+SOC group), or SOC al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 47 publications
(71 reference statements)
0
24
0
2
Order By: Relevance
“… 41 The patch is applied over 30 minutes to the feet and can provide pain relief for weeks-to-months. 107 , 108 Common adverse events include application site pain and erythema, burning sensation, and extremity pain. 88 A recent study found that the capsaicin 8% patch can provide pain relief and improvement in function through nerve regeneration in both DPN and PDPN.…”
Section: Pharmacotherapymentioning
confidence: 99%
“… 41 The patch is applied over 30 minutes to the feet and can provide pain relief for weeks-to-months. 107 , 108 Common adverse events include application site pain and erythema, burning sensation, and extremity pain. 88 A recent study found that the capsaicin 8% patch can provide pain relief and improvement in function through nerve regeneration in both DPN and PDPN.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Studies using a single 30-min 8% capsaicin treatment on diabetic skin showed that reinnervation started around 3 weeks. 90 Full recovery of innervation in healthy human skin after a 60-min single application of capsaicin comprised 24 weeks. 91 More studies are needed as PDL treatment may act differently on the skin compared to capsaicin, and because psoriatic skin is typically hyper-innervated compared to normal or diabetic skin.…”
Section: Reg Row Th Of Nerve S Is Comple X and Time-consumingmentioning
confidence: 99%
“…It is currently unknown what the reinnervation time is for psoriatic nerve fibres after damage to the upper layer of the skin (max 1.2 mm depth 89 ), where PDL therapy is thought to have an effect. Studies using a single 30‐min 8% capsaicin treatment on diabetic skin showed that reinnervation started around 3 weeks 90 . Full recovery of innervation in healthy human skin after a 60‐min single application of capsaicin comprised 24 weeks 91 .…”
Section: Regrowth Of Nerves Is Complex and Time‐consumingmentioning
confidence: 99%
“…63 It has also been shown to provide pain relief in a disease-modifying manner via nerve regeneration and restoration of function in PDPN. 64 A recent publication notes that some patients treated with the capsaicin patch may require two or three treatments before an initial response is observed. 65 Studies have evaluated the application of local anesthetics in PDPN.…”
Section: Symptomatic Pain Treatmentmentioning
confidence: 99%
“…In a randomized, placebo‐controlled study, capsaicin 8% patch has been shown to be effective in relieving pain up to 24 weeks after application 63 . It has also been shown to provide pain relief in a disease‐modifying manner via nerve regeneration and restoration of function in PDPN 64 . A recent publication notes that some patients treated with the capsaicin patch may require two or three treatments before an initial response is observed 65 …”
Section: Treatment Optionsmentioning
confidence: 99%